Electronic Marketing Reality in Elite Players in Iraq - Ahmed, Riaad; Jebar, Abdul Jaleel (Journal of Physical Education, 2021)
The research aimed at identifying the reality of electronic marketing in elite athletes. The researchers used the descriptive method on (193) athletes from different sports; individual and team. Direct questions and an electronic marketing scale were applied to conclude that athletic shows come first in most bought goods. The results showed that there is a difference between direct and electron shopping in favor of direct shopping. In addition to that, the results showed that sports federations do not provide athletes with proper apparels and equipment thus placing financial burdens on the athlete. Finally, the researchers concluded that language was not a barrier in electronic shopping, lack of safety and trust was the main barriers for athletes in electronic shopping.